Media Au-Vi Berbasis PowerPoint dalam Pembelajaran Bahasa Indonesia (SATU Press Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2022)
Learning Indonesian Language nowadays is a challenge for both teachers and students. This condition certainly requires a media to be an intermediary between teachers and students in online and offline learning. Especially, the media that functions as a messanger or delivers the materials from the teacher to students in learning Indonesian language. This media is needed to support Indonesian language learning so that the target is achieved as planned. The objectives of this research include (1) the procedure for making PowerPoint-based Au-Vi media, (2) the factors that influence the making of PowerPoint-based Au-Vi media. This research uses a qualitative method. The process of data analysis of this research is expressed descriptively. The results show that the process of making PowerPoint-based Au-Vi media tends to be easy if the teacher is proficient in using Microsoft PowerPoint. Teachers can create templates, insert learning materials, insert voice explanations for material, add back sounds, set automatic transitions and animations, and save them in MP4 video format. There are two factors that influence the making of this media, namely factors related to the learning components and technical factors outside the learning components.